KARAKTERISTIK SIFAT FISIK DAN KIMIA UBI KAYU (Manihot esculenta) BERDASARKAN LOKASI PENANAMAN DAN UMUR PANEN BERBEDA - Susilawati Susilawati; Siti Nurdjanah; Sefanadia Putri (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2008)
Cassava (Manihot esculenta) is the third primary food in Indonesia after rice and corn. Cassava doesn’t have distinctive harvest period, therefore the harvesting period can be varied and resulting differences physical and chemical properties. Production rate and physical and chemical properties will vary due to soil fertility of cassava plantation. The purpose of this study is to analysis physical and chemical properties at Gunung Agung village Sekampung Udik district and Sinar Baru village Marga Tiga district, at Lampung Timur regency with different harvesting periods. The method used in this study was a descriptive method with two factors : harvesting age and plant location. The results show that Kasetsart variety with ten month of harvesting age at location A (Gunung Agung village Sekampung Udik) had better physical and chemical properties, and these can be seen from the fresh cassava water content (60,67%), cassava density (1,15 g/mL), starch content (35,93%), starch yield (18,94%), starch moisture (8,17%), amilose content (18,03%) and amylopectin content (81,97%) and enzymaticly conversion of starch to glucose (64,92%). Different plan locations and harvesting periods resulted in different physical and chemical properties. These indicated that Kasetsart variety grown at location A is more suitable to be converted to bioethanol compared to those of at location B. Keywords: Bioethanol, harvesting period, Kasetsart cassava, physical and chemical properties.